3rd IEEE International Workshop on Visualizing Software for Understanding and Analysis 2005
DOI: 10.1109/vissof.2005.1684311
|View full text |Cite
|
Sign up to set email alerts
|

The Dominance Tree in Visualizing Software Dependencies

Abstract: Dominance analysis from graph theory allows one to locate subordinated software elements in a rooted dependency graph. It identifies the nesting structure for a dependency graph as a dominance tree, and, hence, adds irnformation not immediately visible irn large and complex graphs. Moreover, the subordirnation (or locality) can be leveraged for drawirng dependency graphs. This paper envisioins ways to leverage the domirnance relation for structurirng and presentirng large dependency graphs. To explore the feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Our experience with this natively supported feature was not demonstrating an expected reduction of the build time as it seems that the job dependencies are resolved in a linear fashion bringing little benefit to the parallel submission. For this reason, we are currently experimenting the reshaping of the bundles software dependency graph under the form of a dominance tree [3] structure where the nodes hold the software within the dependency graph of the bundle, and edges reflect a build dependency. This permits to quickly identify intermediate dominating software which can be built within concurrent jobs.…”
Section: Resif 30 Architecture-at-a-glancementioning
confidence: 99%
“…Our experience with this natively supported feature was not demonstrating an expected reduction of the build time as it seems that the job dependencies are resolved in a linear fashion bringing little benefit to the parallel submission. For this reason, we are currently experimenting the reshaping of the bundles software dependency graph under the form of a dominance tree [3] structure where the nodes hold the software within the dependency graph of the bundle, and edges reflect a build dependency. This permits to quickly identify intermediate dominating software which can be built within concurrent jobs.…”
Section: Resif 30 Architecture-at-a-glancementioning
confidence: 99%
“…Many researchers have investigated the modeling and visualization of dependency graphs [21,17,18,22,30,31,15,23,14,20]. For example, Falke et al suggested a hierarchical graph layout for visualizing the functional dependency graph of software applications; by using a hierarchical layout, users can view the top-level nodes as a first overview and step-wise unfold the nodes on demand to look into details [15]. Dias et al implemented Hunter, a visual tool that includes node-link diagrams as dependency graphs for understanding JavaScript source code [14].…”
Section: Related Workmentioning
confidence: 99%
“…Graph, composed of nodes and edges, is one of the most popular visual representations for software dependencies [1], [3]. Advantages to represent dependencies as a graph are multiple.…”
Section: Introductionmentioning
confidence: 99%